PENGARUH KRISTEN DALAM UPACARA MANGONGKAL HOLI PADA MASYARAKAT BATAK (SEBUAH TINJAUAN ETNOARKEOLOGI) - Defri Elias Simatupang (Berkala Arkeologi Sangkhakala, 2006)
“Mangongkal holi” is the megalithic tradition which is one theprocession of funeral rites in Batak community. It‟s the form ofsecondary burial with digging the skeleton and moved it from primaryburial into the secondary ones. Considering that some of the Batakcommunity who held this activity is Christianity, so “mangokal holi” riteswas influenced by this religion.